The learner corpus path: a worthwhile methodological challenge - Dutra, Deise Prina; Orfanò, Bárbara Malveira; Guedes, Annallena de Souza; Alves, Jessica Ceritello; Fekete, João Gabriel (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
Corpus compilation is a challenging research endeavor that many researchers decide to pursue. Few learner corpora, however, can be easily accessed (e.g.,the International Corpus of Learner English), and none of them carry a variety of text registers written by English learners at different proficiency levels studying in the Brazilian university context. Therefore, the aim of this paper is to present the compilation of a learner corpus, much needed in our research and teaching context, pointing out the advantages of building this type of corpus for the understanding of learners’ needs as well as for pedagogical decision-making based on sound data. Presenting a detailed rationale of the corpus compilation, this article reveals the various decisions made in order to guarantee that fair comparisons can be made. To exemplify the value of building a carefully designed corpus, results of previous studies are compared. Some of the conclusions reached refer to the need for discipline-specific tasks to propel writing proficiency and for authorship skills to be developed in English for Academic Purposes classes to foster academic success.